Python programming : an introduction to computer science - Zelle, John M. (Franklin, Beedle, 2017)
"This book serves as an introduction to computer programming using the Python programming language"-- This third edition of John Zelle's Python Programming continues the tradition of updating the text to reflect new technologies while maintaining a time-tested approach to teaching introductory computer science. An important change to this edition is the removal of most uses of eval and the addition of a discussion of its dangers. In our increasingly connected world, it's never too early to begin considering computer security issues. This edition also uses several new graphics examples, developed throughout chapters 4-12.